Innopolis University - From Zero to Hero Ten Years of Challenges and Victories - Mazzara, Manuel (Springer Nature, 2022)
This open access book describes the development of Innopolis, a young Russian university established in 2012 to focus on teaching excellence in computer science, engineering, and robotics. It reports on the problems that were faced in the first decade of its development, and the adopted solutions. It shows how the key aspects for the development of the faculty, the curricula, the university structure, and the challenge of internationalization have been successfully addressed by the university management and professors, and how the solutions are scalable for other newly founded research organizations. The book is divided in five parts: "The Beginning" describes the very early days in general, from the foundation and start-up of the university with the related processes. "The People" reports on the initial hiring of the faculty members, the selection of students, and the curriculum development. "The Activities" provide information about the creation of the single research institutions and labs, and their relation to industry. "The Future" gives an outlook on the planned internationalization and faculty strategy. Eventually, "A Visual Journey" shows a selection of photographs illustrating highlights of the whole process and the current achievements. The processes and the components described built the basis for the development of Innopolis, and many of them still have a big impact on its present and its future. The fewer mistakes are made at the beginning, the higher the probability to fully achieve the initial goals.